Biocompatible and Biodegradable Surfactants from Orange Peel for Oil Spill Remediation - Wang, P.S. (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Oil spill remediation plays a vital role in mitigating the environmental impacts caused by oil spills. The chemical method is one of the widely recognized approaches in chemical surfactants. However, the most commonly used chemical surfactants are toxic and non-biodegradable. Herein, two biocompatible and biodegradable surfactants were synthesized from orange peel using the ionic liquid 1-butyl-3-methylimidazolium chloride (BMIMCl) and organic solvent dimethylacetamide (CH3CN(CH3)2) as reaction media. The acronyms SOPIL and SOPOS refer to the surfactants prepared with BMIMCl and dimethylacetamide, respectively. The surface tension, dispersant effectiveness, optical microscopy, and emulsion stability test were conducted to examine the comparative performance of the synthesized surfactants. The Baffled flask test (BFT) was carried out to determine the dispersion effectiveness. The toxicity test was performed against zebrafish (Danio rerio), whereas the closed bottle test (CBT) evaluated biodegradability. The results revealed that the critical micelle concentration (CMC) value of SOPIL was lower (8.57 mg/L) than that of SOPOS (9.42 mg/L). The dispersion effectiveness values for SOPIL and SOPOS were 69.78 and 40.30, respectively. The acute toxicity test demonstrated that SOPIL was âpractically non-toxicâ with a median lethal concentration of more than 1000 mg/L after 96 h. The biodegradation rate was recorded as higher than 60 for both surfactants within 28 days, demonstrating their readily biodegradable nature. Considering these attributes, biocompatible and biodegradable surfactants derived from orange peel emerge as a promising and sustainable alternative for oil spill remediation. Â© 2023 by the authors.